A colaboração partidária na formulação da política externa brasileira: 1995 a 2010 - Soares, Hugo Rafael (Universidade Federal do Tocantins, 2021)
Our work aimed to verify the party collaboration during the analyzed governments and the process of production of the Brazilian foreign policy, by the proposals of the parties PSDB and PT, in function of the access to the decision making center of the Brazilian foreign policy, through federal executive. Aiming to delimit the role of parties in relation to the formulation of their foreign policy and demonstrate that it is not an irrelevant or less priority issue for their internal discussions, provoking an ideological debate. Such a condition has allowed the decision-making group to use the institutional arrangements of the Ministry of Foreign Affairs either to promote its political projects - which are the result of systemic, regional, party orientations and proposals - or to filter and constrain ideas contrary to proposals. Methodologically, we undertook a qualitative analysis - an examination of the literature produced on the relationship between the main parties and foreign policy, considering the period in which they remained ahead of the country, through an analysis of the constitutional text, public opinion polls and the Presidential campaign platforms from 1995 to 2010. The results indicated that while formal and informal rules restrict a more purposeful role of parties in foreign policy-making, their actions are not at all irrelevant. In addition, the legislature has control mechanisms that can restrict the scope of executive proposals. In this last sphere parties can also influence the president's decisions regarding the promotion and implementation of policies in the decision-making process.